2008
DOI: 10.1097/sla.0b013e3181856241
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic Response to Severe Burn Injury

Abstract: Objective To improve clinical outcome and to determine new treatment options, we studied the pathophysiologic response postburn in a large prospective, single center, clinical trial. Summary Background Data A severe burn injury leads to marked hypermetabolism and catabolism, which are associated with morbidity and mortality. The underlying pathophysiology and the correlations between humoral changes and organ function have not been well delineated. Methods Two hundred forty-two severely burned pediatric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
649
3
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 527 publications
(682 citation statements)
references
References 91 publications
20
649
3
10
Order By: Relevance
“…Serum AST, ALT, and ALKP are elevated between 50% to 200% from baseline when compared with normal levels (Figure 2). Jeschke et al (16,26) observed that serum AST and ALT peaked during the first day postburn and ALKP during the second day postburn. During hepatic regeneration, all enzymes returned to baseline during acute hospitalization.…”
Section: Hepatic Changes In Response To a Burn And The Hepatic Acutementioning
confidence: 99%
See 2 more Smart Citations
“…Serum AST, ALT, and ALKP are elevated between 50% to 200% from baseline when compared with normal levels (Figure 2). Jeschke et al (16,26) observed that serum AST and ALT peaked during the first day postburn and ALKP during the second day postburn. During hepatic regeneration, all enzymes returned to baseline during acute hospitalization.…”
Section: Hepatic Changes In Response To a Burn And The Hepatic Acutementioning
confidence: 99%
“…These responses are present in all trauma, surgical, or critically ill patients, but the severity, length, and magnitude is unique for burn patients (7). Marked and sustained increases in catecholamine, glucocorticoid, glucagon, and dopamine secretion are thought to initiate the cascade of events leading to the acute hypermetabolic response with its ensuing catabolic state (7,8,26,(61)(62)(63) (Figure 4). The cause of this complex response is not well understood.…”
Section: Glucose Protein and Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The inflammatory cascade is initiated in the wound as signals, including DAMPs, ignite local inflammation. The inflammation, as well as damaged and clogged blood vessels, cause local edema, increased hydrodynamic pressure, I/R injury, and redox imbalance, which contribute to local spreading of tissue damage (burn injury progression) and an immune response that can spillover into the circulation to result in systemwide capillary leak, edema, and the release of large amounts of oxygen and nitrogen radical species.…”
Section: Large Burns Disrupt Homeostasis Systemicallymentioning
confidence: 99%
“…Велика опікова травма викликає суттєві гемодинамічні та кардіодинамічні порушення, які сприяють розвитку сепсису, поліорганної недостат-ності та смерті. Кардіогенний стрес є відмінною ознакою гострої фази відповіді, а гірші результати лікування опікового пошкодження пов'язані саме з важкою серцевою дисфункцією [2,3,6]. Скомпро-метована серцева функція призводить до гіпопер-фузії органів, порушення периферичної мікроцир-куляції, збільшення зони опіку та зниження резис-тентності до бактеріальної інфекції в ділянці опіко-вої поверхні [2].…”
Section: морфологічні зміни у міокарді щурів в умовах інфузійної кореunclassified